PEMBINAAN PENINGKATAN KETERAMPILAN MENGGUNAKAN MICROSOFT OFFICE 2016 PADA MASYARAKAT SEKUPANG - Sasa Ani Arnomo; Yulia Yulia; Nopriadi Nopriadi (PUAN INDONESIA, 2022)
Microsoft Office 2016 is one of the applications in data processing. Regarding community groups, it must be admitted that the community's ability to use Microsoft Office 2016 is minimal, because many people, especially students at the SMP Kampung Baru Indosat Sekupang Batam, do not understand and understand the use of Microsoft Office 2016 applications. The difficulties they experience are: school assignments related to questions in the form of essays related to the tools in Microsoft Office 2016 because the hours of computer subjects are less when compared to hours of other subjects. In addition, understanding of how the Microsoft Office 2016 application works and functions is still minimal. This is where the service team provides guidance in improving using Microsoft Office 2016 with the aim of improving knowledge and understanding skills for students using Microsoft Office 2016 applications.